Factors predicting regression of visual acuity following successful treatment of anisometropic amblyopia - Jia, Yu; Liu, Jing; Ye, Qingqing; Zhang, Shenglan; Feng, Lei; Xu, Zixuan; Zhuang, Yijing; He, Yunsi; Zhou, Yusong; Chen, Xiaolan; Yao, Ying; Jiang, Rengang; et al. (Frontiers in Medicine, 2022)
Objective: Regression of visual acuity when treatment is discontinued is a concern. We aimed to identify factors associated with visual acuity regression following successful treatment of anisometropic amblyopia. Design and Method: This was a retrospective cohort study. Database records for one hundred and sixty-one children with anisometropic amblyopia who met at least one criterion for successful treatment proposed by the Pediatric Eye Disease and Investigator Group (PEDIG) and had at least one year of follow-up data available after the criterion was met were analysed. The study sample was split into two groups, those who regressed within one year of successful treatment (no longer met any of the PEDIG criteria for successful treatment) and those who did not. A two-step analysis involving a least absolute shrinkage and selection operator (LASSO) regression and a logistic regression were used to identify predictor variables for increased risk of regression. A broad range of clinical, perceptual, and demographic variables were included in the analyses. Results: Sixty-eight (42.5%) of children regressed within one year of successful treatment. Lower risk of regression was associated with larger amblyopic eye visual acuity improvement with treatment, younger age at initiation of treatment and female sex. Conclusion: Early detection and treatment of anisometropic amblyopia not only improves treatment outcomes but may also reduce the risk of treatment regression.